2018
DOI: 10.1177/0044118x18791869
|View full text |Cite
|
Sign up to set email alerts
|

Striving and Dreaming: A Grounded Theory of the Transition to Adulthood for Cross-Systems Youth

Abstract: The transition to adulthood is an underresearched topic for cross-systems youth, defined as young people who have experienced homelessness, child welfare system involvement, and educational challenges. This qualitative study explored processes of resilience in the transition to adulthood for cross-systems youth aged 18 to 24 ( n = 20). Analysis of in-depth interviews using a grounded theory open coding process revealed two thematic concepts, striving and dreaming. As illustrated in two case studies, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Thirteen studies reported data of 277 young adults from six countries including eight studies from the United States (Banyard & Williams, 2007; Bickelhaupt et al, 2019; Bowen et al, 2018; Hines et al, 2005; Luther, 2015; Samuels & Pryce, 2008; Suzuki et al, 2008; Thomas & Woodside, 2011), one from Canada (Schofield, 2001), one from Hong Kong (Ho et al, 2019), one from South Korea (Park & Schepp, 2018), one from South Africa (Bain & Durbach, 2018), and one from Israel (Rafaeli, 2017). Concerning the type of ACEs covered, all but two studies (Bowen et al, 2018; Ho et al, 2019) reported on a single type.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported data of 277 young adults from six countries including eight studies from the United States (Banyard & Williams, 2007; Bickelhaupt et al, 2019; Bowen et al, 2018; Hines et al, 2005; Luther, 2015; Samuels & Pryce, 2008; Suzuki et al, 2008; Thomas & Woodside, 2011), one from Canada (Schofield, 2001), one from Hong Kong (Ho et al, 2019), one from South Korea (Park & Schepp, 2018), one from South Africa (Bain & Durbach, 2018), and one from Israel (Rafaeli, 2017). Concerning the type of ACEs covered, all but two studies (Bowen et al, 2018; Ho et al, 2019) reported on a single type.…”
Section: Resultsmentioning
confidence: 99%
“…Our study also highlights the need for policies and programs targeted toward emerging adults who are not engaged in higher education. Participants reported personal and career aspirations that were meaningful but not associated with furthering their education, as well as feeling disconnected or uncertain about how to achieve their educational goals (E. A. Bowen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported personal and career aspirations that were meaningful but not associated with furthering their education, as well as feeling disconnected or uncertain about how to achieve their educational goals (E. A. Bowen et al, 2020). Currently, there is a void in the social safety net for emerging adults who are unconnected to educational systems, particularly for those who experience family instability (Sakala et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations